Capturing chemical intuition in synthesis of metal-organic frameworks - Seyed Mohamad Moosavi (Nature Portfolio, 2019)
Synthetic chemists develop a "chemical intuition" over years of experience in the lab. Here the authors combine machine learning of (partially) failed experiments with robotic synthesis to capture this intuition used in searching for the optimal synthesis conditions of metal-organic frameworks.